Faktor- Faktor yang Mempengaruhi Behavioral Intention Penggunaan Aplikasi Pemesanan Mobile Kopi pada Kalangan Gen Z di DKI Jakarta - Ali, Mohammed Ameen Sallam; Rizan, Mohamad; Parlyna, Ryna (Indo Publishing, 2026)
The rapid development of digital technology has transformed consumer behavior, including in the coffee industry, which increasingly relies on online ordering applications. This study aims to analyze the influence of Performance Expectancy and Social Influence on Behavioral Intention to use coffee ordering applications among Generation Z in DKI Jakarta, with Attitude Toward Using as a mediating variable. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z respondents in DKI Jakarta who have experience using coffee ordering applications and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that Performance Expectancy and Social Influence have a positive and significant effect on Attitude Toward Using. Furthermore, Attitude Toward Using has a positive and significant effect on Behavioral Intention, while Social Influence does not have a direct effect on Behavioral Intention. The indirect effect analysis shows that Attitude Toward Using mediates the relationship between Performance Expectancy and Behavioral Intention as well as between Social Influence and Behavioral Intention. Overall, this study concludes that users’ attitudes play a crucial role in shaping the intention to use coffee ordering applications among Generation Z.